Characterization and application of Bragg‐edge transmission imaging for strain measurement and crystallographic analysis on the IMAT beamline. Issue 2 (26th March 2019) - Ramadhan, Ranggi S.; Kockelmann, Winfried; Minniti, Triestino; Chen, Bo; Parfitt, David; Fitzpatrick, Michael E.; Tremsin, Anton S.
Abstract : Characterization of Bragg‐edge transmission imaging on the new IMAT beamline at the ISIS pulsed neutron source is performed and application of the technique is demonstrated. Bragg‐edge transmission is capable of producing accurate strain maps with high spatial resolution and spatially resolved texture information, non‐destructively. Abstract : This paper presents a series of experiments to characterize the performance of the new IMAT beamline at the ISIS pulsed neutron source and provides examples to showcase the potential applications of Bragg‐edge transmission imaging on the instrument. The characterization includes determination of the IMAT spectral and spatial resolutions through calibration measurements, and also determination of the precision and the accuracy of Bragg‐edge analysis for lattice parameters of ceramics, metals and textured engineering alloys through high‐temperature measurements. A novel Bragg‐edge analysis method based on the cross‐correlation of different Bragg edges has been developed to provide an estimate of the change in lattice parameter, which is especially useful for measurements of textured samples. Three different applications of the Bragg‐edge transmission imaging technique are presented, including strain mapping, texture mapping and obtaining crystallographic information, i.e . the dependence on temperature of the Debye–Waller factor. The experimental results demonstrate the ability of the IMAT beamline to provide accurate strain measurements with uncertainties as low as 90 µϵ with reasonable measurement time, while characteristic materials parameters can be mapped across the sample with a spatial resolution of 300–600 µm for a strain map and down to ∼90 µm for a texture map.